Five-level inverter with dual reference modulation technique for grid-connected PV system - Rahim, N.A.; Selvaraj, J.; Krismadinata, C. (Elsevier, 2010)
This paper presents a single-phase five-level grid-connected PV inverter with a novel dual reference modulation technique. Two reference signals identical to each other with an offset equivalent to the amplitude of the triangular carrier signal were used to generate PWM signals. The inverter consists of a full-bridge inverter and an auxiliary circuit comprising four diodes and a switch. The inverter produces output voltage in five levels: zero, +1/2V(dc), V-dc, -1/2V(dc) and -V-dc. A digital PI current control algorithm is implemented in DSP TMS320F2812 to keep the current injected into the grid sinusoidal and to have high dynamic performance with low THD. The validity of the proposed inverter is verified through simulation and implemented in a prototype. The experimental results are compared with conventional single-phase three-level grid-connected PWM inverter in terms of THD. Crown Copyright (C) 2009 Published by Elsevier Ltd. All rights reserved.